Komunikasi Masyarakat Muslim dalam Membangun Sikap Toleransi di Desa Siborongborong Kabupaten Tapanuli Utara - Siregar, Unnaisah Khairani; Sikumbang, Ahmad Tamrin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This research aims to determine how the Muslim community communicates and builds an attitude of tolerance in Siborongborong Village, North Tapanuli Regency. This research method uses a descriptive qualitative approach with the type of field research. This research data comes from interviews and observations as primary data and relevant literature reviews as secondary data. This research data was analyzed through data reduction, presentation, and verification. The validity of this research data was tested through triangulation techniques. This research shows that communication between Muslim and non-Muslim communities in Siborongborong Village, North Tapanuli Regency, is essential for building tolerance and social harmony attitudes. Village residents can broaden their understanding of religious communities and reduce negative stereotypes through dialogue, discussion, and daily interactions. An attitude of tolerance reflected in mutual respect, appreciation, and assistance strengthens relationships between individuals and builds trust in cultural and religious diversity. Communication and tolerance are the primary keys to maintaining social harmony and diversity in society, making maintaining good communication and strengthening attitudes of tolerance an inevitable priority in efforts to build an inclusive and peaceful society.